Review of the book Amazone. Un monde en partage - Zanotelli, Cláudio Luiz (Geografares, 2025)
Review of the book "Amazone. Un monde en partage", by Hervé Théry. The book is part of the collection “Géohistoire d’un fleuve” published by the prestigious CNRS Éditions. In this book, Théry makes us see and feel the land from the river and makes us rethink the Amazonian territories from a geohistorical perspective.
Keywords: geohistory; river; Amazon